Statistical analysis of apparent morphology and characteristics of corroded rebars of concrete in the marine environment - Ying, Zongquan; Li, Jiamin; Zhao, Juan (Frontiers in Materials, 2024)
The residual cross-sectional areas of corroded rebars and their uniformity are the main indexes to evaluate the safety and durability of concrete structures in the marine environment. To evaluate corrosion characteristics of naturally corroded rebars, nineteen corroded rebars were extracted from the prototype components of a high-pile wharf with 35 years of service. The apparent morphology characteristics of corroded rebars were obtained using 3D scanning. The results indicate that the corrosion is non-uniform along both the longitudinal and cross-sectional directions of the corroded rebars. In the marine environment, the residual cross-sectional areas of corroded rebars along the length adhere to a three-parameter Weibull distribution; however, no specific probability distribution model or clear correlation with the distribution pattern exists for rebars with varying corrosion degrees. The spatial heterogeneity factors of the rebars are characterized by a three-parameter Frechet distribution.